The feelings inferiority of student in Islamic junior high school - Afri Rahmadia Marta; Daharnis Daharnis; Syahniar Syahniar (RedWhite Press, 2018)
Feelings of inferiority in the individual can interfere with his development. Therefore, it is important to provide treatment through Guidance and Counseling services. In order for the implementation of Guidance and Counseling services to run effectively and efficiently, it is necessary described the inferiority condition of individual accurately. This study aims to describe feelings of inferiority student’s in Islamic Junior High School. The research methodology used is quantitative with a descriptive-analysis. The research instrument used Likert scale model. Research subjects amounted to 38 students. The results showed that the feelings inferiority of student was in a medium category with a persentage 50%.